Brand Image, Kualitas Pelayanan Dan Kepuasan Konsumen Di Dalam Pengaruhnya Terhadap Minat Ulang Penggunaan Aplikasi Dana - Lilik Indrawati; Marcell Mathias Pattinama (University of Merdeka Malang, 2021)
The purpose of this study was to determine the effect of brand image, service quality and customer satisfaction on re-interest in using the Dana application. The population in this study were students of Darma Cendika Catholic University, Widya Mandala Catholic University Surabaya and St. Vincetius Paolo University (RKZ). The sample is 75 respondents, with the consideration that this number can represent the research sample. This research method is quantitative with multiple regression analysis, the data entered is processed with SPSS version 20. The results of this study indicate that brand image and service quality do not affect re-interest using Dana application for students in Surabaya, and consumer satisfaction has a significant effect on re-interest in using the Dana application to students in Surabaya.